Pelaksanaan Program Gerakan Literasi Sekolah di SMP Negeri 2 Takalar - Karyani, Syntha Esterlita; Sultan, Sultan; Hasriani, Hasriani (Nuances of Indonesian Language, 2024)
This research aims to: (1) describe the implementation of the habituation stage in the school Literacy Movement program at SMP Negeri 2 Takalar; and (2) describe the implementation of the literacy development stages in the school Literacy Movement program at SMP Negeri 2 Takalar; and (3) describe the implementation of the literacy learning stages in the school Literacy Movement program at SMP Negeri 2 Takalar. The research design used was descriptive qualitative. The data in this research are text descriptions of the habituation stage, development stage and learning stage in the school literacy movement. The data sources in this research are documents of School Literacy Movement (GLS) activities, photos of reading activities, photos of reading corners in class, library photos, and other general data, in the form of recorded data during the observation and interview process. The data collection techniques used in this research are observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The research results revealed that the school literacy movement implemented at SMP Negeri 2 Takalar had three stages, namely the habituation stage, development stage, and learning stage.